A hierarchical model for eco-design of consumer electronic products - Wang, Xiaojun; Chan, Hing Kai; Lee, Carman K. M.; Li, Dong (Technological and Economic Development of Economy, 2015)
Designing environmentally friendly products has become a tighter requirement in the marketplace because of both the increasing trend in awareness of consumers and the obligations from legislation requirements. Unfortunately, this is not a straight forward decision for designers to evaluate whether their design options are satisfactory in terms of balancing various factors (for examples, different forms of environmental assessment) or not. This is partly attributed to the fact that there is no universally accepted approach for conducting such analysis. In this connection, this research makes reference to a European Union (EU) directive as a reference model and makes use of Analytic Hierarchical Process (AHP), which is a useful tool to help designers to make decision, for evaluating eco-design options. The AHP model is developed based on two case studies on consumer electronic products. Pairwise comparisons, one of the key steps in AHP, are conducted with the expertise gained from the case studies and the help from the software package Expert Choice. The paper also reveals how design options can be evaluated, or be screened out. The proposed method does not require the designers to conduct detailed analysis (life-cycle assessment for example) for every new product options and hence can save their time. This is particularly important when they are facing shorter and shorter product life cycle nowadays. First published online: 18 Jun 2014